Evidence-based insecticide resistance in South American tomato leaf miner, Phthorimaea absoluta (Meyrick) under laboratory selection. Issue 3 (15th June 2023) - Prasannakumar, N. R.; Jyothi, N.; Prasadbabu, K.; Ramkumar, G.; Asokan, R.; Saroja, S.; Sridhar, V.
Abstract: The South American tomato moth, Phthorimaea absoluta (Meyrick), is one of the key pests of tomato in India. Since its report in 2014, chemical control has been the main means of tackling this pest, both in the open field and protected cultivation. Despite regular insecticidal sprays, many outbreaks were reported from major tomato-growing regions of South India during 2019–2020. A study was conducted to investigate the effect of insecticide resistance on biology, biochemical enzymes, and gene expression in various P. absoluta field populations viz ., Bangalore, Kolar, Madurai, Salem, and Anantapur to commonly used insecticides such as flubendiamide, cyantraniliprole, and indoxacarb. Increased levels of insecticide resistance ratios (RR) were recorded in P. absoluta populations of different locations. A significant increase in cytochrome P450 monooxygenase (CYP/MFO) and esterase levels was noticed in the resistant population compared to susceptible one. Through molecular studies, we identified four new CYP genes viz ., CYP248f (flubendiamide), CYP272c, CYP724c (cyantraniliprole), and CYP648i (indoxacarb). The expression levels of these genes significantly increased as the folds of resistance increased from G1 to G20 (generation), indicating involvement of the identified genes in insecticide resistance development in P. absoluta . In addition, the resistant populations showed decreased fecundity, increased larval development period, and adult longevity, resulting in more crop damage. The information generated in the present study thus helps in understanding the development of insecticide resistance by P. absoluta and suggests the farmers and researchers to use insecticides wisely by adopting insecticide resistance management as a strategy under integrated pest management.